Early and Late Migrating Avian Individuals Differ in Constitutive Immune Function and Blood Parasite Infections – But Patterns Depend on the Migratory Strategy - Hegemann, Arne; Birberg, Cyndi; Hasselquist, Dennis; Nilsson, Jan-Åke (Frontiers in Ecology and Evolution, 2022)
Billions of birds migrate every year. To conduct a successful migration, birds undergo a multitude of physiological adaptions. One such adaptation includes adjustments of immune function, however, little is known about intraspecies (between-individual) and interspecies (between-species) variation in immune modulations during migration. Here, we explore if early and late migrating individuals differ in their immune function, and if such patterns differ among species with short- versus long-distance migration strategies. We quantified three parameters of baseline (constitutive) innate immune function and one parameter of baseline (constitutive) acquired immune function in 417 individuals of 10 species caught during autumn migration at Falsterbo (Sweden). Early and late migrating individuals differed in lysis and total immunoglobulins, but the patterns show different directions in long-distance migrants (wintering in Africa) as compared to short-distance migrants (wintering within Europe). Specifically, early migrating long-distance migrants had lower lysis but higher immunoglobulin levels than late migrating individuals. In short distance migrants, there was no difference in lysis between early and late migrating individuals, but immunoglobulin levels were higher in late migrating individuals. We found no correlation between timing of migration and haptoglobin, but long-distance migrants had lower levels of haptoglobin than short-distance migrants. We also found that the prevalence of haemosporidian blood parasite infections decreased in long-distance migrants, but increased in short-distance migrants, as the autumn progressed. Taken together, our study suggests that the investment into immune function depends on the migratory strategy (short- vs long-distance migrants), and that early and late migrating individuals of a migration strategy might invest differently in baseline immune function, potentially driven by differences in the trade-offs with timing and speed of migration. Our study highlights the potential adaptations of immune function that could help explain trade-offs with other physiological systems, and behavioural responses during migration.